2020
DOI: 10.1115/1.4046293
|View full text |Cite
|
Sign up to set email alerts
|

Deep Reinforcement Learning for Procedural Content Generation of 3D Virtual Environments

Abstract: This work presents a deep reinforcement learning (DRL) approach for procedural content generation (PCG) to automatically generate three-dimensional (3D) virtual environments that users can interact with. The primary objective of PCG methods is to algorithmically generate new content in order to improve user experience. Researchers have started exploring the use of machine learning (ML) methods to generate content. However, these approaches frequently implement supervised ML algorithms that require initial data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…As a matter a fact, using deep reinforcement learning in playing digital games has one crucial flaw -if the environment that agent trained on is not exactly the same as in the actual game -the method overfits. By using procedural content creation in their training, agent performance became significantly more general [16].…”
Section: Figure 3 -Civilization VI Uses Procedural Content Creation Methods For World Map Customizationmentioning
confidence: 99%
“…As a matter a fact, using deep reinforcement learning in playing digital games has one crucial flaw -if the environment that agent trained on is not exactly the same as in the actual game -the method overfits. By using procedural content creation in their training, agent performance became significantly more general [16].…”
Section: Figure 3 -Civilization VI Uses Procedural Content Creation Methods For World Map Customizationmentioning
confidence: 99%
“…Learners have the ability to experience real environments and be actively involved with the components of the virtual environment, thereby increasing their immersion, interaction, and sense of realism [43]. Three-dimensional virtual environments are an effective way to create interactive environments in which abstract concepts and skills can be developed through problem solving, exploration, and experimentation [44][45][46]. Tilhou et al [47] defined 3D virtual environments as 3D interactive spaces that can be used for various purposes.…”
Section: Three-dimensional Virtual Learning Environmentsmentioning
confidence: 99%
“…Artificial intelligence (AI) will play a central role in modernized training systems for the military. The transformative potential of AI-enhanced training and education is made possible by advancements in a wide array of capabilities, including natural language processing, 1 multimodal learning analytics, 2 automated scenario generation, 3 and adaptive decision-making, 4 that can be leveraged to create engaging and effective training experiences that are tailored to individual learners and teams. Numerous studies have shown that when designed effectively, adaptive instructional systems (AISs), such as intelligent tutoring systems, can be as effective as a skilled human tutor at supporting student learning.…”
Section: Introductionmentioning
confidence: 99%